2018
DOI: 10.3390/polym10091030
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing Property and Adsorption Kinetics of Reactive Dyes for Cotton Textiles in Salt-Free Non-Aqueous Dyeing Systems

Abstract: In recent years, new concepts in textile dyeing technology have been investigated which aim to decrease the use of chemicals and the emission of water. In this work, dyeing of cotton textiles with reactive dyes has been investigated in a silicone non-aqueous dyeing system. Compared with conventional aqueous dyeing, almost 100% of reactive dyes can be adsorbed on cotton textiles without using any salts in non-aqueous dyeing systems, and the fixation of dye is also higher (80%~90% for non-aqueous dyeing vs. 40%~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 51 publications
(57 reference statements)
1
30
0
1
Order By: Relevance
“…This shows that there is a high affinity between fiber and dye. 1) Pseudo-first-order-kinetic model The fitting of the pseudo first-order-kinetic model was done using Langergren's equation [16] ( ) q t (mg/g) and q e (mg/g) are quantity of dye adsorbed at different time t (min)of dyeing and at equilibrium, k 1 is the rate constant of the pseudo first order kinetic model. Using Equation (9) a graph of ( ) ln e t q q − versus t was plotted as shown in Figure 6 and was used to calculate R 2 the correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that there is a high affinity between fiber and dye. 1) Pseudo-first-order-kinetic model The fitting of the pseudo first-order-kinetic model was done using Langergren's equation [16] ( ) q t (mg/g) and q e (mg/g) are quantity of dye adsorbed at different time t (min)of dyeing and at equilibrium, k 1 is the rate constant of the pseudo first order kinetic model. Using Equation (9) a graph of ( ) ln e t q q − versus t was plotted as shown in Figure 6 and was used to calculate R 2 the correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…2) Pseudo-second-order-kinetic model The pseudo second order kinetic model studied with the following equation [16]…”
Section: Resultsmentioning
confidence: 99%
“…With the aim of developing a whole system of D5 reactive dyeing of cotton fibre, Fu et al reported an optimised soaping process for cotton fabric dyed in a D5 suspension dyeing system using Hexadecyl trimethyl ammonium bromide (HTAB) as a soaping agent, and their results showed that the water consumption of the entire process was only 7‐fold that of fabric mass. With the use of different solvents as dyeing media, Wang et al studied the dyeing properties and adsorption kinetics of reactive dyes for cotton woven fabric in a dye/solvent non‐aqueous dyeing system, while Pei et al investigated the diffusion mechanism of an aqueous solution and the swelling of cotton and viscose yarns in a dye/solvent non‐aqueous dyeing system.…”
Section: Development Of a Dye/solvent Suspension Systemmentioning
confidence: 99%
“…One of the major group of contaminant that should be avoided to discharge them in valuable water resources are dyes. Dyes are organic aromatic materials that have many applications in coloring wools, cottons, strings, and other cellulosic materials 2 and classified as basic, anthraquinon, azo, acid, metal complex, disperse, and mordant dyes. Their entrance in water resources causes many problems.…”
Section: Introductionmentioning
confidence: 99%